Fine Soil Texture Is Conducive to Crop Productivity and Nitrogen Retention in Irrigated Cropland in a Desert-Oasis Ecotone, Northwest China - Lisha Wang; Zhibin He; Wenzhi Zhao; Chuan Wang; Dengke Ma (Agronomy, 2022)
Agricultural production in oases requires extensive irrigation and nitrogen (N) inputs, which result in a high incidence of non-point-source pollution. Information on how soil texture affects crop productivity and water and N use efficiency is needed to improve N management in oases. A two-year field study with six free-draining leaching pits was set up to quantify soil water content (SWC), drainage, yield, N uptake, soil residual N, N leaching, water-use efficiency (WUE), and N fertilizer-use efficiency (NFUE) on sandy-textured soils in a young oasis field (24 years, YOF) and loam-textured soils in an old oasis field (>60 years; OOF) within an intensive oasis agricultural zone in Northwest China. The results showed that sand content in the YOF was significantly higher than that in the OOF (p < 0.01), while both clay and silt contents in the YOF were significantly lower than those in the OOF (p < 0.01). Soil water storage (SW) in the 0–100 cm soil layer, evapotranspiration water-use efficiency (WUEET) and irrigation water-use efficiency (WUEIrrig) in the OOF were, respectively, 87.1, 23.5, and 24.1% higher than those in the YOF (p < 0.05), and deep drainage in the YOF was 6.2 times higher than that in the OOF (p < 0.01). Maize N uptake and soil N accumulation in the OOF in the 0–100 cm soil layer were, respectively, 33.4 and 10.3% higher than those in the YOF (p < 0.05), and N leaching loss in the YOF was 1.65 times higher than that in the OOF (p > 0.01). Crop yield and NFUE in the OOF were, respectively, 23.9 and 27.2% higher than those in the YOF (p < 0.05). These results indicated that sandy-textured soils with high sand content were not conducive to water and N retention, resulting in lower crop yields and water- and fertilizer-use efficiency in YOF. Therefore, it is imperative that management practices in sandy-textured land promote improvements in soil structure and maintain the long-term productivity of the young cultivated fields.